Efficacy and tolerability of combination therapy with alpha-blockers and phosphodiesterase-5 inhibitors compared with monotherapy for lower urinary tract symptoms: Protocol for a systematic review and network meta-analysis. Issue 43 (23rd October 2020) - Qiangzhao, Liu; Xiaofeng, Zhang; Fenghai, Zhou; Qiong, Lian; Fa, Zhang; Bohong, Guo; Xinsheng, Xi
Abstract: Purpose: This study aimed to compare the efficacy and safety of combination therapy consisting of α-blockers and different phosphodiesterase type 5 inhibitors for lower urinary tract symptoms (LUTS) by performing a network meta-analysis. Method: Relevant articles were retrieved from the Cochrane Library, PubMed, and EMBASE databases. Bayesian network meta-analyses were performed with a random-effect model to compare the efficacy and safety of combination therapy with α-blockers and phosphodiesterase-5 inhibitors for LUTS. The odds ratio (OR), mean difference (MD) and surface under the cumulative ranking curve (SUCRA) were calculated with the GeMTC R package. Results: Twenty randomized trials with 4131 patients were included in this network meta-analysis. Based on the SUCRA values, vardenafil (10 mg) combined with α-blockers ranked first, first and sixth; sildenafil (25 mg) combined with α-blockers ranked second, third and first; and tadalafil (20 mg) combined with α-blockers ranked third, second and fourth in IPSS, post void residual, and maximum flow rate, respectively. Conclusions: Combination therapy with α-blockers and phosphodiesterase-5 inhibitors was effective and well tolerated for LUTS. For men who prioritize high efficacy, vardenafil (10 mg) combined with α-blockers seems to be the treatment of choice. For men wishing to optimize minimally invasive treatment, sildenafil (25 mg) and tadalafil (20 mg) combined with α-blockers appears to have a possible advantage in terms of avoiding adverse effects. Abstract : Supplemental Digital Content is available in the text